The influence of word of mouth on purchase intentions for Nokia smartphones in Bandung city - Desy Natalia Girsang (Institute of Computer Science (IOCS), 2023)
Along with the development of the era and technology, the markets of the smartphone industry are getting bigger. Each smartphone company is competing with each other to create the most sophisticated products. This condition affected the sale of the Nokia phone, which experienced a decline in sales from 2013 until now. This brand no longer appears in consumers' minds. This is due to the need for more consumer knowledge and the perception of the Word of Mouth on Nokia. Thus, Word of Mouth is needed by Nokia to increase its sales. This research aims to analyze the effect of Word of Mouth on consumers' purchase intention of Nokia smartphones in Bandung. This research was conducted by using descriptive methods and statistical verification analysis. The population used in this study are consumers who have purchased smartphones in Bandung. The sample used in this study are consumers who use Nokia smartphones and recognize the Nokia brand, using a non-probability sampling technique of 100 respondents. The data collection process has been done through the distribution of questionnaires and several literature studies. The analytical method used in this research is simple linear regression analysis, while the research hypothesis will be tested using a t-test. Based on the research results, Word of Mouth positively affects consumer purchase intentions by 59.4%, with the results of hypothesis testing having a significant effect.